FRAUD PENTAGON THEORY IN DETECTING FRAUDULENT FINANCIAL REPORTING IN FINANCIAL COMPANY - Sapiri, Muhtar; Sulistyawati, Ardiani Ika; Muklis, Muklis; Alfiana, Alfiana; Putro, Rizki Listyono (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Indonesia's banking sector has experienced recurrent fraud incidents, particularly those involving falsified financial statements, revealing persistent vulnerabilities despite heightened regulatory scrutiny. These issues position banking and financial services as one of the most fraud-prone industries in Indonesia, necessitating a deeper understanding through advanced frameworks like the fraud pentagon theory, which identifies pressure (Financial Target) as a primary driver of dishonest reporting, alongside opportunity (Financial Stability), rationalization (Change in Auditor), competence (Change in Director), and arrogance (CEO’s Photo Frequency). This study utilizes secondary data obtained from the IDX, with 30 companies as samples, resulting in 150 panel data points from the banking and financial sector in Indonesia. The data was analyzed using Eviews. The research indicate that only the financial target variable, proxied by ROA, has a positive and significant effect. Meanwhile,the other variables are insignificant, although the variables financial stability, change in auditor, and change in director show a negative direction. The implications of these findings suggest that by increasing its application in developing market environments and demonstrating that not all proxies suggested for ability and arrogance have predictive power in non-Western environments like Indonesia, where cultural and institutional factors can reduce their relevance, this research advances the Fraud Pentagon Theory. Specifically, this casts doubt on the universality of arrogance as an incentive for deception, arguing that the visual depiction of leadership is more consistent with enhancing corporate image than with dishonesty.